Thermal absorber material selection for solar thermal Bi‐Metallic multilayer crosses absorber - Abd Razak, Nuradhiathy; Abdul Majid, Zafri Azran; Ruslan, Mohd Hafidz; Sopian, Kamaruzaman (Institute Advanced Science Extension (IASE), 2016)
The energy gain term determines the level of energy received by the solar absorber from solar radiation and various methods have been implemented to increase the collector performance using a bi-metallic cross absorber. Experiments have been conducted to determine suitable material pairing between the bi-metallic cross absorber and black coated flat-plate absorber. Five types of solar thermal absorbers are investigated under condition 525 W/m2 of solar radiation and with 0.52 m/s air flow speed in terms of heating and cooling performance. Four set stainless steel cross absorbers achieved best energy retention capability by obtaining the slope value of -0.1520 during the cooling phase while during the heating phase, coated flat plate performed well with a slope value of 0.4909. The profile of the thermal absorber with thermal absorption and thermal buffer can be summarized using a spider chart with distance index bar-chart, and the result shows that a bi-metallic, aluminium and stainless steel cross absorber exhibit the optimal balanced thermal profile. With the implementation of the material selection method could minimize the material selection process for cross absorber application.